Analisis Modal Kerja dan Leverage terhadap Profitabilitas serta Implikasinya pada Nilai Perusahaan Manufaktur di Bei - Muhammad Pikar; M. Radityatama; Rian Fransisco; Agiel Pranata; Winstoon Yordan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study aims to examine the effect of working capital efficiency and leverage on profitability and its implications for firm value in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2025 period. The post-COVID-19 pandemic condition has increased operational risks for manufacturing companies due to fluctuations in interest rates, exchange rates, cash management, inventories, and receivables. Therefore, companies are required to implement more effective financial strategies to maintain competitiveness. Profitability is positioned as an intervening variable because previous studies showed inconsistent results regarding the relationship between working capital efficiency, leverage, profitability, and firm value. This research uses a quantitative approach with path analysis to examine direct and indirect relationships among variables. The population consists of all manufacturing companies listed on the IDX, while the sample includes 45 companies selected from 270 firms using purposive sampling based on specific criteria, such as consistent listing and financial performance. The results indicate that working capital efficiency has a significant positive effect on profitability, leverage has a significant negative effect on profitability, profitability significantly increases firm value, and profitability fully mediates the effect of working capital efficiency and leverage on firm value. These findings provide theoretical and practical implications for managers and investors in financial decision-making.